PEMUTUSAN HUBUNGAN KERJA SEPIHAK ANTARA PT. INDAH KIAT DENGAN TENAGA KERJA BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Muhammad Fahrurrozi; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Termination of employment within the company often creates problems, especially layoffs for efficiency reasons such as granting workers' rights as compensation for layoffs. Employers often give workers rights that are less suitable and often workers / laborers are asking for their rights beyond the provisions set forth in legislation.The method used in writing this skiripsi is to make a sociological approach that is by doing research in the field. Termination of Employment that occurred caused by many factors ranging from laborers, employers, law or by the court. Termination of Employment because efficiency is categorized as layoff by company / entrepreneur. Procedures and procedures for the settlement of termination of employment are regulated in Law Number 2 Year 2004, but the procedures for termination of employment due to efficiency are not specifically regulated in this law.Based on research results, it is concluded that Termination of Employment conducted by PT. Indah Kiat is not in accordance with the mechanism of Termination of Employment which is in the rules of the company itself and not in accordance with the provisions of articles 151 and 161 of Act number 13 of 2003 on Manpower. Efforts made in the settlement of termination of this employment is to make decisions properly and correctly. Termination of Employment can not be made without the approval of the industrial relations settlement court and without the consent of both parties.Keywords: Termination of Separate Working Relations - worker - PT. Indah Kiat